Depression in people with type 2 diabetes: current perspectives - Darwish L (Dove Medical Press, 2018)
Lina Darwish,1–4 Erika Beroncal,1–3 Ma Veronica Sison,1–3 Walter Swardfager1–4 1Hurvitz Brain Sciences Program, Sunnybrook Research Institute, Toronto, ON, Canada; 2Department of Pharmacology and Toxicology, University of Toronto, Toronto, ON, Canada; 3Cardiac Rehabilitation Program, University Health Network Toronto Rehabilitation Institute, Toronto, ON, Canada; 4Canadian Partnership for Stroke Recovery, Toronto, ON, Canada Abstract: Type 2 diabetes mellitus (T2DM) is associated with depressive symptoms, and comorbid depression in those with T2DM has been associated with adverse clinical profiles. Recognizing and addressing psychological symptoms remain significant clinical challenges in T2DM. Possible mediators of the reciprocal relationship between T2DM and depression may include physical activity levels, effectiveness of self-management, distress associated with a new T2DM diagnosis, and frailty associated with advanced diabetes duration. The latter considerations contribute to a “J-shaped” trajectory from the time of diagnosis. There remain significant challenges to screening for clinical risks associated with psychological symptoms in T2DM; poorer outcomes may be associated with major depressive episodes, isolated (eg, anhedonic), or subsyndromal depressive symptoms, depressive-like symptoms more specific to T2DM (eg, diabetes-related distress), apathy or fatigue. In this review, we discuss current perspectives on depression in the context of T2DM with implications for screening and management of these highly comorbid conditions. Keywords: type 2 diabetes, depression, mood, complications